Role of the local government in provision of public goods : a case study of Bayandai district, Russian federation - Khaykhadaeva, Oktyabrina (2014)
The local government is that level of government which is the most close to people (voters). Among all levels of government, it is the best informed about local needs and preferences. It should play significant role in the provision of local public goods. In this work it is studied how in practice the local government in the Russian Federation fulfills its tasks, namely what role the local government plays in the provision of educational and health services.